THE ESSENCE AND FORMATION FOUNDATIONS OF THE CORRUPTION PHENOMENON - Shakarov Oybek Xudoyberdi ogli (The Conference Hub, 2025)
This work explores the essence of the corruption phenomenon and the fundamental factors behind its formation. It examines the social, political, and economic conditions that foster corruption, identifying both systemic issues and individual behaviors contributing to its proliferation. Additionally, the research delves into the moral and ethical implications of corruption within society and its impact on governance, law enforcement, and public trust. By analyzing various theoretical frameworks, the study aims to shed light on effective measures and strategies to prevent and combat corruption in contemporary societies.
Keywords: corruption, phenomenon, social impact, political governance, ethical standards, prevention strategies, public trust, moral implications, economic factors, anti-corruption policies.